Interactional Techniques Used in Class Opening and Closing in EFL Classes (Siddhajyoti Interdisciplinary Journal, 2023)
The present article attempts to investigate the interactional techniques employed by the basic level teachers to begin and end English language classes. For this purpose, 15 English as Foreign Language (EFL) teachers who have been teaching English at basic level in Banke district were purposively selected as the participants of the study. The data was collected employing an observational technique. Each of the observed classes was audio recorded and then transcribed. The transcribed data was analyzed based on thematic technique of qualitative data analysis. The findings showed that teachers engaged in several interactional micro actions that were included in the class starting and ending moves. A variety of interactional techniques including greeting students, calling names, checking the assigned homework and phatic communion were found to be used by the teachers to begin the classes. Similarly, interactional techniques such as assigning homework and describing the upcoming lessons were found to be the most common sub-moves used to close the lesson.